The role of pilgrimage to Mecca (Hajj) in gaining moral virtues and avoiding moral vices - Rezae, Mohammad Jaefar; Najafi, Mohammad; Majyd Mahygyer, Abdul; Masood Keshavarz, Seyed (Pure and Applied Science Advances, 2014)
The goal of research is to study about the traninig role of Haj in the present society. This paper considers the role of Haj in creating and strengthening social mutual understanding as well as gaining moral virtues and avoiding moral vices. This objective is achieved by analyzing Quran verses, muslim Imams' quotions and the commandments of religious men. This is a descriptive analyzing study which it has been done based on a series of reliable resources. Haj is an important religious duty with different dimensions such as personal , social , cultural , educational, economic , and political; if the pilgrims to Mecca (Hajjis) and the officials of education system consider these features, they can get plenty of spiritual achievements. In addition to acknowledging the great journey of Hajj, its educational effects in different.